Allergy and coronavirus disease (COVID-19) international survey: real-life data from the allergy community during the pandemic - Tanno, Luciana Kase; Demoly, Pascal; Martin, Bryan; Berstein, Jonathan; Morais Almeida, Mario; Levin, Michael; Fiocchi, Alessandro; Sánchez Borges, Mario; Caraballo, Luis R.; Wong, Gary W.K.; Ortega Martell, José Antonio; Rouadi, Philip W.; et al. (Lippincott Williams & Wilkins, 2021)
Background: The COVID-19 outbreak brought an unprecedented challenge to the world. Knowledge in the field has been increasing exponentially and the main allergy societies have produced guidance documents for better management of allergic patients during this period. However, few publications so far have provided real-life data from the allergy community concerning allergy practice during the COVID-19 outbreak. Therefore, we proposed an international survey on the management of allergic patients during the current pandemic. Methods: We performed an online survey undertaken to reach out the worldwide allergy community by e-mail and social media. The web-based questionnaire contained 24 questions covering demographic data from the participants, clinical practice during this period, and questions related to the new international classification and coding tools addressed for COVID-19. It was circulated for 8 weeks and had anonymous and volunteer context. Results: Data are presented for 635 participants from 78 countries of all continents. Allergists with long-term professional experience were the main audience. As expected, we received many responses as “I have no data” or “I don’t know” to the questions of the survey. However, most with more experience on managing allergic patients during the pandemic agreed that patients suffering from allergic or hypersensitivity conditions have no increased risk of contracting COVID19 or developing SARS CoV-2. Also, participants mentioned that none of the allergy treatments (inhaled corticosteroids, allergen immunotherapy, biological agents) increased the risk of contracting COVID-19 infection including severe presentations. Conclusion: The data presented are a starting point in the process of getting feedback on all the recommendations provided by the allergy societies; it could also be the basis of new strategies to support health professionals while new COVID-19 specific treatments and vaccines are being explored. The information here presented intends to be helpful to the community but represents a course of action in a highly specific situation due to the state of emergency, and it should be helpful to health systems.